The effect of omega-3 fatty acids and its combination with statins on lipid profile in patients with hypertriglyceridemia: A systematic review and meta-analysis of randomized controlled trials - Yang, Yunjiao; Deng, Wen; Wang, Yanmei; Li, Tongyi; Chen, Yiding; Long, Cong; Wen, Qing; Wu, Yue; Chen, Qiu (Frontiers in Nutrition, 2022)
Background/Aim Omega-3 fatty acids (OM3-FA), a promising treatment for high triglycerides, have gradually attracted public attention. However, some studies showed that their application presented tricky problems, like increasing low-density lipoprotein cholesterol (LDL-C) levels. This study aimed to systematically evaluate the effect of OM3-FA or their combination with statins on the lipid profile in patients with hypertriglyceridemia. Materials and methods This study followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA 2020) guidelines. PubMed, Embase, Web of science, and Cochrane library were searched up to May 15, 2022. The random-effects model was applied to calculate the mean difference (MD) and associated 95% confidence intervals (CI). Results This meta-analysis included 32 studies with 15,903 subjects. When OM3-FA was used as monotherapy compared with placebo, it significantly decreased TG (MD: −39.81, 95% CI: −54.94 to −24.69; p < 0.001), TC (MD: −2.98, 95% CI: −5.72 to −0.25, p = 0.03), very low-density lipoprotein cholesterol (VLDL-C) (MD: −25.12, 95% CI: −37.09 to −13.14; p < 0.001), and non-high-density lipoprotein cholesterol (non-HDL-C) levels (MD: −5.42, 95% CI: −8.06 to−2.78; p < 0.001), and greatly increased LDL-C (MD: 9.10, 95% CI: 4.27 to 13.94; p < 0.001) and HDL levels (MD: 1.60, 95% CI: 0.06 to 3.15; p = 0.04). Regarding apolipoprotein B (Apo-B) and apolipoprotein AI (Apo-AI), no significant effect was identified. When OM3-FA was combined with statins, significant reductions were observed in the concentrations of TG (MD: −29.63, 95% CI: −36.24 to −23.02; p < 0.001), TC (MD: −6.87, 95% CI: −9.30 to −4.45, p < 0.001), VLDL-C (−20.13, 95% CI: −24.76 to −15.50; p < 0.001), non-HDL-C (MD: −8.71, 95% CI: −11.45 to −5.98; p < 0.001), Apo-B (MD: −3.50, 95% CI: −5.37 to −1.64; p < 0.001), and Apo-AI (MD: −2.01, 95% CI: −3.07 to −0.95; p < 0.001). However, the combined therapy did not exert significant changes on the levels of high-density lipoprotein cholesterol (HDL-C) and LDL-C compared to control group. Conclusion The use of OM3-FA either as monotherapy or in combination with statins may potentially reduce the levels of TG, TC, VLDL-C, non-HDL-C, Apo-B, and Apo-AI while increasing the levels of LDL-C and HDL-C. Nevertheless, the effects of OM3-FA observed in this review should be interpreted with caution due to the high heterogeneity between the included studies. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42022329552].